Conjugation of haematopoietic stem cells and platelets decorated with anti-PD-1 antibodies augments anti-leukaemia efficacy. (November 2018) - Hu, Quanyin; Sun, Wujin; Wang, Jinqiang; Ruan, Huitong; Zhang, Xudong; Ye, Yanqi; Shen, Song; Wang, Chao; Lu, Weiyue; Cheng, Ke; Dotti, Gianpietro; Zeidner, Joshua; et al.
Abstract Patients with acute myeloid leukaemia who relapse following therapy have few treatment options and face poor outcomes. Immune checkpoint inhibition, for example, by antibody-mediated programmed death-1 (PD-1) blockade, is a potent therapeutic modality that improves treatment outcomes in acute myeloid leukaemia. Here, we show that systemically delivered blood platelets decorated with anti-PD-1 antibodies (aPD-1) and conjugated to haematopoietic stem cells (HSCs) suppress the growth and recurrence of leukaemia in mice. Following intravenous injection into mice bearing leukaemia cells, the HSC–platelet–aPD-1 conjugate migrated to the bone marrow and locally released aPD-1, significantly enhancing anti-leukaemia immune responses, and increasing the number of active T cells, production of cytokines and chemokines, and survival time of the mice. This cellular conjugate also promoted resistance to re-challenge with leukaemia cells. Taking advantage of the homing capability of HSCs and in situ activation of platelets for the enhanced delivery of a checkpoint inhibitor, this cellular combination-mediated drug delivery strategy can significantly augment the therapeutic efficacy of checkpoint blockade. The systemic administration of haematopoietic stem cells conjugated to anti-PD-1-decorated platelets in leukaemic mice promotes the delivery of the checkpoint inhibitor to the bone marrow and suppresses the growth and recurrence of leukaemia.